Disparitas Hukum terhadap Tindak Pidana Pembunuhan: Studi Kasus Putusan Nomor 424/Pid.B/2023/PN Jkt.Pst dan Putusan Nomor 221/Pid.B/2023/PN Dpk. - Cahyadi, Roby; Fitryantica, Agnes (PT Elaborium Elevasi Indonesia, 2025)
Sentencing disparity has long been a legal issue in Indonesia. Different sentences given by judges for similar cases have led to social jealousy. Therefore, this research will examine the elements that cause the disparity of punishment against the perpetrators of the crime of murder in violation of Article 339 of the Criminal Code (KUHP). This research is a normative legal research conducted by analysing secondary sources or legal and primary materials. This research uses literature study and collects the necessary data. To examine the data obtained, this research uses a qualitative method with a systematic process of data processing and interpretation. This study found that the disparity in the two decisions was that the Defendant Muhammad Yusup alias Yusup alias Mamang Bin Misdi (Alm) in Decision Number 424/Pid.B/2023/Pn Jkt.Pst, who was sentenced to 17 years in prison, had mitigating elements and aggravating elements that were normative. Whereas the Defendant Haris Sitanggang, Son of Parlindungan Sitanggang in Decision Number 221/Pid.B/2023/Pn Dpk who was sentenced to life imprisonment, has no mitigating elements and has aggravating elements, namely the defendant is a member of the police and is carrying out an official criminal sentence from the Indonesian National Police.